Pengaruh dan Perkembangan Terbaru dalam Teknologi Kecerdasan Buatan - Mohammad Fadly, S.E, M.M, Mohammad Fadly, S.E, M.M (Profilm Jurnal Ilmiah Ilmu Perfilman dan Pertelevisian, 2024)
Technological advancements, changes in consumer behavior, technological accessibility, social media, streaming services, and advancements in production technology have all led to exponential growth in digital audio and video production. With media convergence, the distinction between audio and video media becomes unclear. This makes multimedia content more flexible. However, changing business models,copyright issues, and content quality are also affected by this phenomenon. The development of digital audio and video production has experienced significant exponential growth, influenced by technologicaladvancements, changes in consumer behavior, technological accessibility, social media, streaming services, and advances in production technology. Media convergence has blurred the boundaries between audio and video media, creating flexibility in multimedia content. However, this phenomenon also has an impact on changing business models, content quality, and copyright issues. Copyright issues are taking center stage in the industry, especially with the rise of video sharing and streaming platforms. Copyright protection is a major challenge, and the law must constantly adapt to technological advances. The methodological approach carried out in this study is called literature research. The result of the discussion was that alternative business models such as subscribe, crowdfunding, and partnerships became strategies to address copyright issues. By studying media convergence, recommendation algorithms, copyright issues, business models, and user roles can help us to understand and control complex developments in digital audio and video production. To maintain the integrity of this industry, ethical guidelines and responses to technological trends must be created.